Passenger Train passing through a Trinidad Oilfield. B.W.I. S 3 – 8 - (:unkn) unknown (James Book Store, 2010)
From 1882 the Trinidad Government Railway passenger trains passed through oilfields on the way to San Fernando. The passengers in this train would see oil derricks in the field and a long shed, with thatched roof, surrounded by dozens of barrels of oil.
Colour: Black and White; Style: Landscape; Other: Unbordered; Divided
Keywords: Trinidad and Tobago; Postcards; Petroleum industry and trade--Trinidad and Tobago; Oil fields--Trinidad and Tobago; Cranes, derricks, etc.--Trinidad and Tobago; Trees--Trinidad and Tobago; Barrels--Trinidad and Tobago; Sheds--Trinidad and Tobago; Men--Trinidad and Tobago; Railroad trains--Trinidad and Tobago; Thatched roofs--Trinidad and Tobago; Transportation--Trinidad and Tobago